Type I Endoleak Following Covered Stent Graft Placement for Traumatic Subclavian Artery Pseudoaneurysm - Ishan Kumar; Md. Sharoon Ansari; Ashish Verma; Pramod Kumar Singh; Ratnesh Kumar (Journal of Clinical Interventional Radiology ISVIR, 2024)
Subclavian artery pseudoaneurysm is an uncommon entity caused by trauma or iatrogenic arterial injury. Endovascular management is the preferred treatment strategy but can be complicated by endoleaks. We report a case of type I endoleak occurring after endovascular covered stent placement to treat a traumatic pseudoaneurysm of proximal left subclavian artery.